In-situ polymerized solid-state electrolytes with stable cycling for Li/LiCoO2 batteries. (January 2022) - Geng, Zhen; Huang, Yuli; Sun, Guochen; Chen, Rusong; Cao, Wenzhuo; Zheng, Jieyun; Li, Hong
Abstract: Interfacial issues between solid-state electrolytes and electrodes are considered as one of key problems hindering the performance improvement of solid-state lithium batteries. In-situ polymerization is one of the most promising methods for improving interfacial performance, where liquid-state electrolytes are in-situ converted into solid-state electrolytes within the battery. It could effectively reduce interfacial resistance, meanwhile, it could enable compatibility of commercial production devices of Li-ion batteries. Here, a new kind of liquid-state electrolyte used for in-situ polymerization is designed based on previously reported high-temperature-resistant electrolyte. Small amounts of LiPF6 play dual roles in prevention of aluminum (Al) current collector corrosion and acceleration of in-situ polymerization of 1, 3-dioxolane (DOL) solvent inside the cell at room temperature. Interfacial stability between in-situ polymerized electrolyte and LiCoO2 cathode is improved by the formation of interfacial layer with good stability during the electrochemical process, due to synergistic effects of added fluoroethylene carbonate (FEC) and hexamethylene diisocyanate (HDI) with the assistance of proton. Reaction mechanism between FEC and HDI is analyzed by DFT calculations. It shows good electrochemical performance in 4.2 V Li/LiCoO2 cell at room temperature. It provides the possibility of designing high-voltage solid-state lithium metal battery by in-situ polymerization and electrochemically interfacial engineering methods. Graphical Abstract: The solid-state lithium battery is designed by an in-situ polymerization strategy. The 4.2 V Li/LiCoO2 cell is constructed by DOL in-situ polymerization, combining with the formation of interfacial layer containing fluorine and nitrogen composites during the electrochemical process. It provides the possibility of the design of high-voltage solid-state lithium metal battery by in-situ polymerization and electrochemically interfacial engineering methods. ga1 Highlights: In-situ polymerization used in high-voltage Li batteries is developed. Side reactions at the interface of SSE and LiCoO2 are effectively suppressed. Stable interfacial layer is formed by actions of FEC and HDI with proton assistance. Reaction mechanism of FEC and HDI is analyzed by DFT calculations. Li/LiCoO2 cell shows good cycling performance at 4.2 V after 500 cycles at RT.